1999
DOI: 10.1212/wnl.52.6.1221
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of the dopamine transporter in progressive supranuclear palsy and Parkinson’s disease

Abstract: Patients with PD have a more pronounced loss of dopamine transporters in the posterior putamen due to a subdivisional involvement of nigrostriatal dopaminergic projections in idiopathic PD. This technique is useful in the determination of neurochemical changes underlying PD and PSP, thus differentiating between them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Recently, Ilgin and associates reported the similar results as this study using 11 C-WIN 35,428 PET imaging of the DAT in PSP and PD [42]. They demonstrated a more pronounced loss of DATs in the posterior putamen in patients with PD.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, Ilgin and associates reported the similar results as this study using 11 C-WIN 35,428 PET imaging of the DAT in PSP and PD [42]. They demonstrated a more pronounced loss of DATs in the posterior putamen in patients with PD.…”
Section: Discussionsupporting
confidence: 85%
“…However, it has been suggested that 18 F-dopa assessment might overestimate the number of striatal dopaminergic nerve terminals in early stage of PD, because the loss of dopaminergic synapses is partially compensated for by increased dopamine turnover in the surviving terminals [2,[7][8][9][10]. An alternative radiotracer binding target is dopamine transporter (DAT), which has been visualized by 11 C-cocaine [11], 11 C-RTI-32 [12], 11 C-CFT [13], 18 F-CFT [14] and 18 F-FP-CIT [5]. FPCIT is a highaffinity cocaine analog binding specifically to DAT.…”
Section: Introductionmentioning
confidence: 99%
“…For this specific aim, it seems that positron emission tomography (PET) imaging performs better than single photon emission computerized tomography because of its higher resolution. For PET imaging, several DAT radioligands labeled with 11 C have now been proposed (Leenders et al, 1990;Guttman et al, 1997;Ilgin et al, 1999). However, as 18 F can be more largely used for clinical purposes than 11 C because of its longer physical period (110 versus 20 min), there is an increasing need to make available high-performance radioligands labeled with 18 F. To date several cocaine derivatives labeled with 18 F have been developed such as FPCIT (Chaly et al, 1996;Kazumata et al, 1998;Ma et al, 2002), N-(3-fluoropropyl)-2␤-carbomethoxy-3␤-(4-bromophenyl)nortropane (FPCBT) (Chaly et al, 2004), 2␤-carbomethoxy-3␤-(4-fluorophenyl)tropane (CFT) (Haaparanta et al, 1996;Laakso et al, 1998;Nurmi et al, 2000), 2␤-carbomethoxy-3␤-(4-chlorophenyl)-8-(3-fluoropropyl)nortropane (FPCT) (Goodman et al, 1997), and N-2-fluoroethyl-2␤-carbomethoxy-3␤-(4-chlorophenyl)-nortropane (FECNT) (Goodman et al, 2000;Deterding et al, 2001;Davis et al, 2003).…”
mentioning
confidence: 99%